2014
DOI: 10.1002/bab.1128
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen‐producing Escherichia coli strains overexpressing lactose permease: FTIR analysis of the lactose‐induced stress

Abstract: The lactose permease gene (lacY) was overexpressed in the septuple knockout mutant of Escherichia coli, previously engineered for hydrogen production from glucose. It was expected that raising the lactose transporter activity would elevate the intracellular lactose concentration, inactivate the lactose repressor, induce the lactose operon, and as a result stimulate overall lactose consumption and conversion. However, overexpression of the lactose transporter caused a considerable growth delay in the recombinan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…This experiment confirmed that little or no lactose molecule penetrates inside lon cells by either other facilitated transport systems or diffusion and LacY is required for the disaccharide internalization ( Figure 10 A). However, a deleterious effect on cell viability was observed in lacY + cells, resembling a “lactose killing” phenomenon [ 46 ]. Surprisingly, the comparison of the growth behaviors of recombinant KrPL lacY + bearing pP79- lacZ and pP79 highlights that the cause of the observed stress is not related to the de-energization caused by elevated transmembrane lactose transport.…”
Section: Discussionmentioning
confidence: 99%
“…This experiment confirmed that little or no lactose molecule penetrates inside lon cells by either other facilitated transport systems or diffusion and LacY is required for the disaccharide internalization ( Figure 10 A). However, a deleterious effect on cell viability was observed in lacY + cells, resembling a “lactose killing” phenomenon [ 46 ]. Surprisingly, the comparison of the growth behaviors of recombinant KrPL lacY + bearing pP79- lacZ and pP79 highlights that the cause of the observed stress is not related to the de-energization caused by elevated transmembrane lactose transport.…”
Section: Discussionmentioning
confidence: 99%
“…The FT-IR spectrum can be used for both qualitative and quantitative analyses of chemical components and is thus highly informative for analysis of multicomponent samples. FT-IR spectroscopy is thus a wellregarded analytical method for evaluation, monitoring and analysis of various biotechnological processes [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%